Factors influencing training effectiveness towards job satisfaction among non-academic employees in UNIMAS / Sarena binti Haidir - Haidir, Sarena (2015)
This study investigated the training factors which were influencing the training effectiveness and job satisfaction among non-academic employees in University Malaysia Sarawak (UNIMAS). The target of study was the non-academic employees in UNIMAS. Two hundred and seventy-nine respondents participated in the survey.